The association between vitamin B12, folate, homocysteine levels, and carotid intima-media thickness in children with obesity: a cross-sectional study - Söbü, Elif; Düzkalır, Hanife Gülden; Özcabı, Bahar; Kaya-Özçora, Gül Demet (De Gruyter Open Ltd, 2022)
Background We aimed to evaluate the association between vitamin B12, folate, homocysteine levels, and carotid intima-media thickness (CIMT) among children with obesity in whom vitamin deficiencies are more frequent. Methods Herein, 100 children with obesity (58 girls) were included (age, 5-18 years). Height, weight, body mass index (BMI), waist circumference (WC), puberty stage, blood pressure, and biochemical values were collected from medical records; standard deviations (SDS) and percentiles were calculated. Obesity was defined as BMI SDS of >+2SDS. Vitamin B12 and folate levels of <300 pg/mL and <4.8 ng/mL, respectively, were considered deficient. A radiologist quantified measurements from the carotid artery. Results Mean patient age was 12.52 +/- 3.63 years. The mean weight SDS, BMI SDS, and WC/height were +3.37 +/- 0.93, +2.93 +/- 0.55, and 0.65 +/- 0.05, respectively. In pubertal cases, insulin (p<0.001), the homeostatic model assessment for insulin resistance (HOMA-IR) (p=0.001) and homocysteine (p=0.002) levels were higher; vitamin B12 (p<0.001) and folate (p<0.001) levels were lower than those in prepubertal ones. WC and HOMA-IR correlated with CIMT; however, homocysteine levels were not correlated with CIMT. Conclusions In our study, pubertal cases had lower vitamin B12 and folate levels as well as higher homocysteine levels. Although no correlation was identified between homocysteine levels and CIMT, this condition may be related to our study group comprising children, who had a shorter duration of obesity than those in adults. As CIMT was higher in children/adolescents with increased WC, it is proposed that they need central obesity more frequently and carefully follow-up.
Keywords: carotid intima-media thickness; folate; homocysteine; ınsulin resistance; vitamin B12; reaxys Chemistry database information